An integrative compositional modeling framework for cross-cultural co-creation of multiespecies dulce de leche in the southern cone - Bruna B. Durço; Sofía Vargha; Elson R. Tavares Filho; Eliane Teixeira Mársico; Adriano G. da Cruz; Paula Cardinal; Graciela Rodriguez; Maria Carmela K.H. Duarte; Lorena Garitta; Adriana Gámbaro; Erick A. Esmerino (Food Quality and Preference, 2026)

Seasonal variations in sources of dissolved inorganic carbon in the Godavari estuary (India) using stable carbon isotopes - R. Sreevidhya; V. R. D. Ghosh; B. S. K. Kumar; S. Pullyottum-Kavil; R. Chakrabarti; D. Cardinal; V. V. S. S. Sarma (Environmental Science and Pollution Research, 2025)

Impairments in reinforcement learning do not explain enhanced habit formation in cocaine use disorder - T. V. Lim; R. N. Cardinal; G. Savulich; P. S. Jones; A. A. Moustafa; T. W. Robbins; K. D. Ersche (Psychopharmacology, 2019)

Dopamine D2-like receptor stimulation blocks negative feedback in visual and spatial reversal learning in the rat: behavioural and computational evidence - Johan Alsiö; Benjamin U. Phillips; Júlia Sala-Bayo; Simon R. O. Nilsson; Teresa C. Calafat-Pla; Arazo Rizwand; Jessica M. Plumbridge; Laura López-Cruz; Jeffrey W. Dalley; Rudolf N. Cardinal; Adam C. Mar; Trevor W. Robbins (Psychopharmacology, 2019)

The diversification of neopasiphaeine bees during the Cenozoic (Hymenoptera: Colletidae) - Eduardo A. B. Almeida; Laurence Packer; Gabriel A. R. Melo; Bryan N. Danforth; Sophie C. Cardinal; Fábio B. Quinteiro; Marcio R. Pie (Zoologica Scripta, 2019)
The biogeography of colletid bees as a whole can be explained by several South American‐Australian trans‐Antarctic interchanges. Within Colletidae, neopasiphaeine bees form a large group that has not been adequately studied, even though they are interesting both from the biogeographical viewpoint for fitting well the austral Gondwanan track and for their associations to host plants. The present paper integrates phylogenetic, biogeographic and paleontological data to reconstruct the evolutionary history of Neopasiphaeinae, with special emphasis on the New World taxa, relating the evolution of these bees to changes, such as the Andes uplift and expansion of open vegetation biomes. First, we propose a phylogenetic hypothesis for the Neopasiphaeinae using one mitochondrial and five nuclear loci. Phylogenetic relationships and divergence time estimation were simultaneously inferred in a Bayesian framework, and the tempo of neopasiphaeine diversification was investigated using lineage‐through‐time plots. The historical biogeography of neopasiphaeine bees was investigated in a likelihood framework. The clade represented by Neopasiphaeinae is strongly supported within Colletidae, and the bulk of their genera can be divided into two major sister‐clades that diverged during the Eocene: one endemic to the Australian region and the other to the Neotropical region. Divergence times among most neotropical genera of Neopasiphaeinae indicate that they differentiated and started their diversification during the Miocene. Our results depict a complex process of geographic evolution in the Neotropical clade, which probably relates to important changes in the neotropical climates and biota beginning at the Oligocene and became more marked in the Miocene. We present a scenario of the neotropical Neopasiphaeinae initially associated with areas of open vegetation in subtropical and temperate portions of South America, followed by multiple separations of lineages east and west of the Andes, and more recent occupations of habitats in tropical portions of the continent.

Identification of a soybean rust resistance gene in PI 567104B - Min Liu; Shuxian Li; Sivakumar Swaminathan; Binod B. Sahu; Leonor F. Leandro; Andrea J. Cardinal; Madan K. Bhattacharyya; Qijian Song; David R. Walker; Silvia R. Cianzio (Theoretical and Applied Genetics, 2016)

High diversity in an urban habitat: are some animal assemblages resilient to long-term anthropogenic change? - Benoit Guénard; Adrianna Cardinal-De Casas; Robert R. Dunn (Urban Ecosystems, 2015)

Reduction of apoptosis in the amygdala by an A2A adenosine receptor agonist following myocardial infarction - M. Boucher; B. P. Wann; S. Kaloustian; R. Cardinal; R. Godbout; G. Rousseau (Apoptosis, 2006)